STRATEGY OUTLINE FOR MARYLAND OCCUPATIONAL SAFETY AND HEALTH REGULATIONS (Tufts Archival Research Center, 2007)
Report outlining a strategy by the Tobacco Institute to attack proposed regulations of Maryland Occupational Safety and Health (MOSH) to ban smoking in enclosed workplaces. Proposes targeting certain groups who may be opposed in order to form a coalition against MOSH. Targets grassroots organizations, the printed press and economic data as being useful resources.